2023
DOI: 10.3390/polym15122683
|View full text |Cite
|
Sign up to set email alerts
|

Material Extrusion of Multi-Polymer Structures Utilizing Design and Shrinkage Behaviors: A Design of Experiment Study

Abstract: Material extrusion (ME) is an additive manufacturing technique capable of producing functional parts, and its use in multi-material fabrication requires further exploration and expansion. The effectiveness of material bonding is one of the main challenges in multi-material fabrication using ME due to its processing capabilities. Various procedures for improving the adherence of multi-material ME parts have been explored, such as the use of adhesives or the post-processing of parts. In this study, different pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
3
8
0
Order By: Relevance
“…The parameters R t and R z are not strongly influenced by printing parameters, unlike R a which increases with layer thickness for both analyzed materials. This observation is in accordance with the literature findings [ 45 , 46 , 63 ], where it is specified that a high layer thickness results in an increased R a .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The parameters R t and R z are not strongly influenced by printing parameters, unlike R a which increases with layer thickness for both analyzed materials. This observation is in accordance with the literature findings [ 45 , 46 , 63 ], where it is specified that a high layer thickness results in an increased R a .…”
Section: Resultssupporting
confidence: 93%
“…Figure 15 , Figure 16 and Figure 17 also reveal that the most significant factor influencing the surface roughness is layer thickness. The same conclusion is presented in [ 46 ], where it was found that the layer thickness had a contribution percentage for R a of 51.56%, whereas layer composition contributed only 4.10%.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The build orientation is considered as one of the manufacturing factors of printing cost and time. Al-Tamimi et al conducted experimental investigations to assess the influence of printing parameters-specifically layer thickness, nozzle temperature, printing speed, raster angle, and layer composition (ABS-PLA)-on various aspects of the printed material [32]. These aspects include mechanical properties, such as bonding modulus, compression modulus, and strength, as well as surface roughness (Ra, Rz, Rku, and Rsk), and dimensional variations related to shrinkage.…”
Section: Related Workmentioning
confidence: 99%
“…Over the years, MEX has been adopted in numerous sectors, including composites [ 4 ], scaffolds [ 5 ], energy harvesting [ 6 ], pharmaceuticals [ 7 ], and home applications [ 8 ]. Moreover, MEX is playing a significant role in the recycling and recovery of different thermoplastic composites [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%